KONSELING ISLAM DENGAN INTEGRASI STOIKISME UNTUK OPTIMALISASI KESADARAN EMOSI SISWA DI SMKN 1 SUMEDANG - Nurrohmah Awaliah, Sintia; Sugandi Miharja; Aam Kurnia (UIN Sunan Kalijaga Yogyakarta, 2025)
This study aims to develop an Islamic Guidance and Counseling (BKI) service model integrating Stoicism principles to enhance emotional awareness among vocational high school students. This holistic approach combines Stoic wisdom with Islamic spirituality. A descriptive qualitative method was employed, using semi-structured written interviews, participant observation, and documentation involving 27 students of SMKN 1 Sumedang. Data were analyzed using the Miles and Huberman model with triangulation for validity. The findings indicate: (1) students initially lacked systematic emotional identification strategies, which improved through Islamic-Stoic reflective approach; (2) integrative counseling services effectively helped students understand and manage emotions rationally and spiritually; (3) significant improvement in emotional awareness based on indicators K1–K11; and (4) a systematic Stoicism-based Islamic counseling service unit was designed for replication in schools. These findings provide conceptual, methodological, and practical contributions to integrative Islamic Guidance and Counseling. Keywords: Islamic Counseling Guidance, Stoicism, Emotional Awareness, Adolescents